Efforts to Increase Income of PT Angkasa Pura Ii Through Cargo and Logistics Business Services Managed By Subsidiaries (PT Angkasa Pura Kargo) - Mohamad Holik Muardi; Edi Abdurachman; Jermanto Setia Kurniawan (Dinasti Publisher, 2024)
This research explores the new strategy PT Angkasa Pura II (AP II) adopted as an airport operator to innovate to increase revenue through its subsidiary PT Angkasa Pura Kargo (APK) in the cargo business through a canvas model approach. This research identifies the potential for business development in cargo services, PT Angkasa Pura II through its subsidiary, namely PT Angkasa Pura Kargo (APK) so that it can run cargo business directly, especially at Soekarno-Hatta International Airport. By improving cargo services, it is hoped to it will be directly proportional to increasing PT Non Aero's income. Angkasa Pura II This research carries out 2 stages of analysis, namely analyzing cargo estimates for the coming year and developing existing business models to create new business models that are opportunities to increase income using canvas business analysis. Based on the analysis results, it was found that the potential demand for cargo at Soekarno-Hatta International Airport shows an increasing trend of 4.67% per year. Based on this data, business opportunities to increase non-aero income through cargo business services can still be possible by carrying out business development carried out by PT APK.